Modeling the Impact of HIV-1 Nucleic Acid Testing Among Symptomatic Adult Outpatients in Kenya. (15th August 2022) - Hamilton, Deven T.; Agutu, Clara; Babigumira, Joseph B.; van der Elst, Elise; Hassan, Amin; Gichuru, Evanson; Mugo, Peter; Farquhar, Carey; Ndung'u, Thumbi; Sirengo, Martin; Chege, Wairimu; Goodreau, Steven M.; et al.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Background: Up to 69% of adults who acquire HIV in Kenya seek care before seroconversion, providing an important opportunity for early diagnosis and treatment. The Tambua Mapema Plus (TMP) trial tested a combined HIV-1 nucleic acid testing, linkage, treatment, and partner notification intervention for adults aged 18–39 years with symptoms of acute HIV infection presenting to health facilities in coastal Kenya. We estimated the potential impact of TMP on the Kenyan HIV epidemic. Methods: We developed an agent-based network model of HIV-1 transmission using TMP data and Kenyan statistics to estimate potential population-level impact of targeted facility-based testing over 10 years. Three scenarios were modeled: standard care [current use of provider-initiated testing and counseling (PITC)], standard HIV rapid testing scaled to higher coverage obtained in TMP (scaled-up PITC), and the TMP intervention. Results: Standard care resulted in 90.7% of persons living with HIV (PLWH) knowing their status, with 67.5% of those diagnosed on treatment. Scaled-up PITC resulted in 94.4% of PLWH knowing their status and 70.4% of those diagnosed on treatment. The TMP intervention achieved 97.5% of PLWH knowing their status and 80.6% of those diagnosed on treatment. The percentage of infections averted was 1.0% (95% simulation intervals: −19.2% to 19.9%) for scaled-up PITC and 9.4% (95% simulation intervals: −8.1% to 24.5%) for TMP. Conclusion: Our study suggests that leveraging new technologies to identify acute HIV infection among symptomatic outpatients is superior to scaled-up PITC in this population, resulting in >95% knowledge of HIV status, and would reduce new HIV infections in Kenya.